Comparison of Oil Palm Empty Fruit Bunch Delignification at Room and Mild Temperature - Lidya Elizabeth; Emmanuela Maria Widyanti; Bambang Soeswanto; Dini Sri Wahyuni; Kartika Dian Pratiwi (Politeknik Negeri Malang, 2022)
Oil palm empty fruit bunches (OPEFB) is one kind of palm oil industry solid waste. OPEFB contains high lignocellulose for about 81-89% that can be used for production of fertilizer, paper, filler, and composite. The separating method of lignocellulose into cellulose, lignin, and hemicellulose can be carried out by delignification using H2O2 and MnSO4.H2O as catalyst. Two experimental designs were performed using the Minitab 21 program with Response Surface Methodology (RSM). Both designs have temperature as their dependent variable. The processes are carried out at 36oC and room temperature with the same variable independent, such as delignification time and concentration of the catalyst. The difference between these two designs is in their stirring process. Delignification that occured at 36oC is processed under constant stirring, while delignification that occured at room temperature is processed without stirring. This experiment aims to determine the optimum conditions for using Mn-catalyst in delignification by varying the time and catalyst concentration. The results show that the lowest lignin content in delignification with reflux is 19.71% (w/w), and for delignification without reflux is 18.24% (w/w). The optimum condition obtained by RSM for reflux delignification was at 6,83 hours with use of 11,03% (w/w) catalyst. Meanwhile, without reflux delignification, the optimum condition was at 3,38 days with a 3.76% (w/w) catalyst.